القواعد التربوية المستنبطة من سورة الإسراء : دراسة تحليلية في ضوء التحديات المعاصرة - شحي, محمد عبد الله محمد سليم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research aimed at deduction of educational rulings from the Qur'anic chapter known as Surat Al-Isra̕ as well as analytic study in the light of contemporary challenges. The researcher presented the verses of the aforementioned Qur'anic chapter with their interpretations from authorized books of Tafsir, and deduced from them educational rules underpinned by proofs from both the Qur'an and Sunnah. The educational rules comprise four aspects which are al-ʽIbadah (worship), al-iman (faith), al-Akhlaq (ethics), and al-Suluk (behavior), and their impacts on individuals, family, and society. Following that are the practical applications in some aspects, shedding light on the contemporary challenges and how they are addressed by the Surah. The research tackled the problem of the study by devising educational rules from the verses of Surat al - Isra to be of help to students of science with different disciplines, as will benefit the specialists in the educational interpretation of the Holy Quran. The inductive approach was employed to draw out some specific scientific instances from authorized books of Tafsir in order to arrive at educational rules. Moreover, the analytical approach was employed to study the specific scientific instances drawn out by deducing a number of important educational rules. The researcher arrived at a number of findings the most important of which are: introduction of a new definition to educational rules, extraction of these rules from the verses due to their invisibility as well as addressing arising contemporary issues while dealing with the extracted rules in the Surah.